Efficacy and safety of Chinese herbal medicine in the treatment of chronic pruritus: A systematic review and meta-analysis of randomized controlled trials - Wang, Jie; Chen, Yuhang; Yang, Xinwei; Huang, Jianli; Xu, Yihua; Wei, Wei; Wu, Xianbo (Frontiers in Pharmacology, 2023)
Background: Chronic pruritus (CP) is a common and aggravating symptom associated with skin and systemic diseases. The treatment of CP is challenging owing to its complex pathogenesis and multiple contributing factors. According to clinical reports, Chinese herbal medicine (CHM) is safe and effective in CP treatment, but evidence to prove it is lacking. Therefore, we conducted this systematic evaluation. Methods: Nine databases were searched for relevant randomized controlled trials (RCTs) from database inception to April 20, 2022. RCTs that compared CHM or a combination of CHM and Western medicine (WM) with WM as a treatment intervention for patients with CP were selected. We evaluated the effects of treatment with CHM on the pruritus degree, Dermatology Life Quality Index (DLQI) score, response rate, recurrence rate, and incidence of adverse events in patients with CP. The risk of bias in each trial was evaluated using the Cochrane Collaboration tool. Meta-analyses were conducted using RevMan software (version 5.3) for calculating comparative effects. Results: In total, 24 RCTs were considered in this meta-analysis. We compared CHM groups with placebo/WM groups and CHM and WM combination groups with WM groups. Meta-analyses were conducted for pruritus severity (by using the visual analog scale), DLQI score, effective rate, recurrence rate, and adverse effect rate. Conclusion: Limited evidence shows that CHM ameliorates CP, and CHM can significantly reduce the degree of pruritus, improve DLQI scores, and mitigate other problems in patients. However, the quantity and quality of studies available in the literature warrant the need for high-quality studies to verify the conclusions.